Biologically Active TNIIIA2 Region in Tenascin-C Molecule: A Major Contributor to Elicit Aggressive Malignant Phenotypes From Tumors/Tumor Stroma - Iyoda, Takuya; Fujita, Motomichi; Fukai, Fumio (Frontiers in Immunology, 2020)
Tenascin (TN)-C is highly expressed specifically in the lesions of inflammation-related diseases, including tumors. The expression level of TN-C in tumors and the tumor stroma is positively correlated with poor prognosis. However, no drugs targeting TN-C are currently clinically available, partly because the role of TN-C in tumor progression remains controversial. TN-C harbors an alternative splicing site in its fibronectin type III repeat domain, and its splicing variants including the type III-A2 domain are frequently detected in malignant tumors. We previously identified a biologically active region termed TNIIIA2 in the fibronectin type III-A2 domain of TN-C molecule and showed that this region is involved in promoting firm and persistent cell adhesion to fibronectin. In the past decade, through the exposure of various cell lines to peptides containing the TNIIIA2 region, we have published reports demonstrating the ability of the TNIIIA2 region to modulate distinct cellular activities, including survival/growth, migration, and invasion. Recently, we reported that the signals derived from TNIIIA2-mediated β1 integrin activation might play a crucial role for inducing malignant behavior of glioblastoma (GBM). GBM cells exposed to the TNIIIA2 region showed not only exacerbation of PDGF-dependent proliferation, but also acceleration of disseminative migration. On the other hand, we also found that the pro-inflammatory phenotypic changes were promoted when macrophages are stimulated with TNIIIA2 region in relatively low concentration and resulting MMP-9 upregulation is needed to release of the TNIIIA2 region from TN-C molecule. With the contribution of TNIIIA2-stimulated macrophages, the positive feedback spiral loop, which consists of the expression of TN-C, PDGF, and β1 integrin, and TNIIIA2 release, seemed to be activated in GBM with aggressive malignancy. Actually, the growth of transplanted GBM grafts in mice was significantly suppressed via the attenuation of β1 integrin activation. In this review, we thus introduce that the TNIIIA2 region has a significant impact on malignant progression of tumors by regulating cell adhesion. Importantly, it has been demonstrated that the TNIIIA2 region exerts unique biological functions through the extremely strong activation of β1-integrins and their long-lasting duration. These findings prompt us to develop new therapeutic agents targeting the TNIIIA2 region.